PENGARUH KUALITAS PELAYANAN, HARGA, DAN FASILITAS TERHADAP KEPUASAN KONSUMEN PADA KAPAL PENUMPANG KM. NAPOLEON RUTE PERJALANAN KENDARI-WANCI (STUDI KASUS PT. AKSAR SAPUTRA LINES) - Asmina Rahmawati; Rois Arifin; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT               This study aims to determine and analyze the influence of Service Quality, Prices and Facilities on Consumer satisfaction on KM passenger ships. Napoleon route Kendari-Wanci (Case Study of PT. Aksar Saputra Lines) partially or simultaneously. The population and sample were all KM economy class passengers. Napoleon which numbered 96 passengers. Data collection through questionnaires. Data analysis in the study using SPSS version 16. The sampling technique using non probability sampling is purposive sampling. The criteria of respondents in this study were KM economy class passengers. Napoleon route Kendari-Wanci. The testing technique of retrieving the data used in this study includes the instrument test, classic assumption test, multiple linear regression test and hypothesis test.                The results of the analysis show that partially the reliability variable does not significantly influence customer satisfaction. While partially the responsiveness, assurance, empaty, price and facilities variables significantly influence customer satisfaction. Simultaneously shows that the realibility variable responsiveness, assurance, empaty, price and facilities significantly influence customer satisfaction.Keywords: Service Quality, Price, Facilities and Consumer Satisfaction